Long-term Survival of HeLa Tumours in Mice Treated with Antilymphocyte Serum - Franks, C. R. (Nature Publishing Group, 1973)
During studies of the ability of antilymphocyte serum (ALS) to suppress the immune mechanism of mice and thereby allow HeLa cells to grow into a large tumour in the mice, it was observed that many tumours continued to grow even after the ALS treatment had been stopped and full immunological competence of the mice had returned. The HeLa cells of such tumours appeared to be unchanged in their ability to induce further tumours in ALS treated mice to which they were transferred and, furthermore, the mice which were carrying such tumours in the presence of immunological competence were able to reject additional injections of HeLa cells or other human tumour cells. The four possible explanations for this phenomenon, (i) depression of cellular response; (ii) local reaction at the graft site; (iii) the presence of a blocking factor; and (iv) the elevation of the humoral response, have been investigated.